PMM.26 Audit of Hypertension in Pregnancy. (9th June 2014) - Wood, SD; Roberts, AL
Abstract : Hypertensive disorders are one of the commonest disorders encountered during pregnancy and carry an increased risk for both mother and baby. A retrospective audit was carried out on the antenatal care of 30 women presenting to Nottingham City Hospital with pre-eclampsia or gestational hypertension from August 2013. Care was audited against the NICE and local Trust guidelines with a standard of 80% (NICE guideline CG107, 2010). Key results from this audit include: It should also be noted that in 17% of cases, no formal diagnosis was recorded. This audit highlighted some training issues with both junior medical staff and midwives. Recommendations made from this audit are further teaching sessions regarding hypertension in pregnancy during junior doctor induction. This is because it is mainly junior doctors making an initial assessment of these patients in Maternity Assessment, perhaps contributing to a lack of diagnosis in 17% of patients. A proforma may also be developed to create a "checklist" helping to ensure that all aspects of clinical management are implemented. A re-audit has been recommended in 6 months' time to allow these recommendations to be put into place.